ANALISIS KAPASITAS SUPLAI AIR BERSIH BAGI PELANGGAN UPTD PENGELOLAAN AIR MINUM (PAM) DI PERUMNAS GRIYA SEJAHTERA - Erwan Yudianto; Lily Endah Diansari (JURNAL ILMIAH BERING'S, 2020)
The fulfillment of The clean Water needs residents of Perumnas Griya Sejahtera, Pagaralam City managed by the UPTD Publis Water Utilities (PAMS). The water supply from the source of water derived from the intake Gunung Dempo, Antan Delapan. Perumnas Griya Sejahtera was became a customer of UPTD Publis Water Utilities (PAMS) since 2018. To that year, It was registered 95 domestic connections. In the following years there was an enhancemet, in 2019 was 167 connections and in 2020 was 254 connections. But for non domestic connection there was only 1 connection. The research aimed to determine the capacity of streamed water supply to Perumnas Griya Sejahtera Pagaralam City now and to know the sufficient of clean water needs for the next 10 years (2030). The study used arithmetic methods, geometry and last-square. Based on the results of the analysis was known that the water discharge UPTD Publis Water Utilities (PAMS) for Perumnas Griya Sejahtera was 1,974 liters/sec or 5.287.161,6 liters/month. Total Clean water needs of Perumnas Griya Sejahtera customers in 2030 was 6,469 liters/sec or 17.322.589,2 liter/month. So that it could be deduced water discharge UPTD Publis Water Utilities (PAMS) for Perumnas Griya Sejahtera was not enough for the customers Perumnas Griya Sejahtera until the year 2030.